2020
DOI: 10.1007/s00330-020-07080-5
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance parametric mapping of the spleen for non-invasive assessment of portal hypertension

Abstract: Objectives In patients with advanced liver disease, portal hypertension is an important risk factor, leading to complications such as esophageal variceal bleeding, ascites, and hepatic encephalopathy. This study aimed to determine the diagnostic value of T1 and T2 mapping and extracellular volume fraction (ECV) for the non-invasive assessment of portal hypertension. Methods In this prospective study, 50 participants (33 patients with indication for trans-jugular intrahepatic portosystemic shunt (TIPS) and 17 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
(43 reference statements)
3
13
0
Order By: Relevance
“…Another promising MRI technique is relaxometry including ECV calculation. Significant correlations between hepatic T1, T2 as well as ECV with liver fibrosis have been already sufficiently described in the previous studies [ 17 , 20 , 21 , 37 39 ]. Liver fibrosis is defined as the accumulation of extracellular matrix proteins produced by fibrogenic cell populations in response to tissue injury.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Another promising MRI technique is relaxometry including ECV calculation. Significant correlations between hepatic T1, T2 as well as ECV with liver fibrosis have been already sufficiently described in the previous studies [ 17 , 20 , 21 , 37 39 ]. Liver fibrosis is defined as the accumulation of extracellular matrix proteins produced by fibrogenic cell populations in response to tissue injury.…”
Section: Discussionsupporting
confidence: 67%
“…Liver fibrosis is defined as the accumulation of extracellular matrix proteins produced by fibrogenic cell populations in response to tissue injury. As a consequence, this process leads to extension of extracellular space and increased accumulation of extracellular MRI contrast agent, which is reflected by prolonged T1 relaxation times and increased ECV of liver [ 21 ]. However, there is still no sufficient data proving correlations between MRE-derived liver stiffness and mapping parameters in patients with PSC.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the MR-elastography, there are novel protocols measuring extracellular volume or Liver Inflammation and Fibrosis score, not requiring a specific device to measure portal pressure (141)(142)(143). This technique is mainly validated for fibrosis, but it also correlates with portal pressure as shown in animals (142)(143)(144). Still significant efforts are required to make it ready to the wide-use in the clinic, but it may be interesting as an one-stop-shop diagnostic approach.…”
Section: Non-invasive Toolsmentioning
confidence: 99%
“…Patients with chronic liver disease (CLD) and, in particular, cirrhosis have a high risk of developing clinically significant portal hypertension (CSPH) [1,2]. CSPH is associated with potentially fatal complications, such as variceal hemorrhage, ascites, hepatic encephalopathy, renal dysfunction, and adverse outcomes after liver surgery and transarterial chemoembolization [2][3][4][5][6]. Currently, liver cirrhosis is the fourth leading cause of death in the adult population of Central Europe and is responsible for approximately 170,000 deaths annually in Europe, and the majority of deaths are not due to hepatocyte failure but instead are due to complications associated with CSPH [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…MRE allows a noninvasive quantitative measurement of the hepatic and splenic stiffness [16], which may represent a helpful biomarker for the characterization of patients with CSPH, as an increased splenic stiffness is associated with CSPH and gastroesophageal varices [17,18]. Recently, the T1 mapping-derived extracellular volume fraction (ECV) of the spleen has been shown to be able to distinguish between healthy volunteers and patients with severe portal hypertension undergoing a transjugular intrahepatic portosystemic shunt (TIPS) procedure [6]. This proof-of-concept study has demonstrated that MR T1 mapping techniques have good potential, not only when measured in the liver but also in the spleen.…”
Section: Introductionmentioning
confidence: 99%